Digital-Based Literacy Analysis of Religious Moderation: Study on Public Higher Education Students - Fahmi Sahlan; Eva Dwi Kumala Sari; Rika Sa'diyah (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2022)
The purpose of this study was to find out the sources of religious Literacy for Private College students in Bekasi City based on increasing their religious insight, as well as to find out which sources were related to religious moderation. The digital-based religious literacy sources referred to in this study are religious sources and networks of religious resources commonly accessed by students to increase religious insight and knowledge. This study uses a descriptive quantitative approach with survey—research data collection by questionnaire, using google form. Document data or questionnaires are analyzed for their content to conclude reflectively. The results showed 1) the enthusiasm of students in finding sources of digital-based religious literacy was tremendous, students tended to seek religious information of their choice through the Internet and social media they had, including surfing on Google, Instagram, Youtube, Facebook, WhatsApp, Tiktok, and religious websites. 2) religious literacy is chosen by students seeking religious insight through the preacher who is active in cyberspace because they consider listening to lectures via the Internet to be practical, easy to obtain, and easy to understand the contents of the lectures. 3) the platforms or websites they visit tend to be mainstream lecturers. Therefore, it is necessary to pay special attention to the rectorate and the Ministry of Religion to explore the contents accessed by students to create religious moderation among students.